2007
DOI: 10.4161/cbt.6.5.4007
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced inactivation or gene silencing of class I histone deacetylases suppresses ovarian cancer cell growth: Implications for therapy

Abstract: There is an urgent need to develop new strategies to treat ovarian cancer, the most deadly gynecologic malignancy. Histone deacetylase (HDAC) inhibitors are emerging as novel therapeutic drugs in the treatment of a variety of cancers, including those resistant to standard chemotherapy. Since there are multiple HDAC isoforms, determining the precise role of individual HDAC isoenzymes in the growth and progression of ovarian cancer has the potential to influence the use of selective HDAC inhibitors as strategic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 29 publications
3
110
0
1
Order By: Relevance
“…These findings are also consistent with the growth inhibitory effects of HDAC inhibitors on colon cancer cells (Archer et al, 1998;Wilson et al, 2006). Although it is known that class I HDACs are consistently up-regulated in human colon cancer and in other solid tumors at the mRNA and/or protein levels (Zhu et al, 2004;Huang et al, 2005;Wilson et al, 2006;Khabele et al, 2007), relatively less is known about HDAC4 expression in colon cancer. Although down-regulation of HDAC4 mRNA in human colon tumor tissue compared with normal has been shown (Lleonart et al, 2006), we detected no overall difference in HDAC4 protein expression between in a panel of matched human colon tumor-normal pairs (unpublished observations) in which clear overexpression of HDAC1, HDAC2, and HDAC3 was detected previously (Wilson et al, 2006).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…These findings are also consistent with the growth inhibitory effects of HDAC inhibitors on colon cancer cells (Archer et al, 1998;Wilson et al, 2006). Although it is known that class I HDACs are consistently up-regulated in human colon cancer and in other solid tumors at the mRNA and/or protein levels (Zhu et al, 2004;Huang et al, 2005;Wilson et al, 2006;Khabele et al, 2007), relatively less is known about HDAC4 expression in colon cancer. Although down-regulation of HDAC4 mRNA in human colon tumor tissue compared with normal has been shown (Lleonart et al, 2006), we detected no overall difference in HDAC4 protein expression between in a panel of matched human colon tumor-normal pairs (unpublished observations) in which clear overexpression of HDAC1, HDAC2, and HDAC3 was detected previously (Wilson et al, 2006).…”
supporting
confidence: 75%
“…A large body of literature indicates that HDAC inhibitors induce cell cycle arrest, differentiation, and apoptosis in colon cancer cell lines in vitro (Heerdt et al, 1994;Mariadason et al, 1997;Archer et al, 1998;Litvak et al, 1998;Mariadason et al, 2000Mariadason et al, , 2001bGurvich et al, 2004;Wilson et al, 2006). Based on such studies, several HDAC inhibitors, including depsipeptide, SAHA, MS-275, and valproic acid, are in clinical trials for the treatment of hemopoetic and solid tumors, including colon cancer (Mei et al, 2004;Bolden et al, 2006;Rasheed et al, 2007), with SAHA recently being approved for the treatment of patients with cutaneous T cell lymphoma.Several studies have demonstrated increased expression of the class I HDACs, HDAC1, HDAC2, and HDAC3, in multiple human cancers, including colon cancer (Zhu et al, 2004;Huang et al, 2005;Wilson et al, 2006;Khabele et al, 2007). Consistent with the ability of HDAC inhibitors to induce maturation in colon cancer cell lines, individual class I HDACs can repress p21 expression, promote cell proliferation and survival, and inhibit differentiation in vitro ( Wilson et al, 2006).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Multiple HDAC enzymes have been identified, of which HDAC1 to HDAC10 are expressed in malignant cells (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). To understand the spectrum of HDACs inhibited by droxinostat and determine whether selective HDAC inhibition is sufficient to sensitize cells to FAS and TRAIL, we examined the spectrum of HDAC enzymes inhibited by droxinostat.…”
Section: Droxinostat Selectively Inhibits Hdac3 Hdac6 and Hdac8mentioning
confidence: 99%
“…Disease Specific patient Survival (DSS) in serous, mucinous, and clear cell carcinomas had no statistical significant but in endometrioid ovarian cancer had negative impact on patient survival [46,47]. The use of the biomarker for hyperacetylation of histones [both in blood lymphocytes and tumor cells] has been useful as a guide to target specificity in early studies of HDAC inhibitors, and this biomarker has been the most extensively developed so far.…”
Section: Brain Tumors Hdac9 Hdac11mentioning
confidence: 99%